Radiographic study of the prevalence of apical periodontitis and endodontic tratment in the adult population of São Luís, MA, Brazil Estudo radiográfico da prevalência de periodontite apical e tratamento endodôntico na população adulta de São Luís, MA, Brasil - Analúcia Guerra Terças; Ana Emília Figueiredo de Oliveira; Fernanda Ferreira Lopes; Etevaldo Matos Maia Filho (University of São Paulo, 2006)
This study investigated the prevalence of apical periodontitis (AP) and its association with endodontically treated teeth in residents of São Luís, MA, Brazil. Two-hundred complete series of periapical radiographs taken over a 10-year period (1993-2003) were retrieved from the files of four prosthesists and five periodontists. The Periapical Index (PAI) was used and the age range, sex, tooth groups, location and association with endodontic treatment (ET) were also analyzed. The Cohen Kappa and Chi-square tests were used for statistical analysis. Out of 200 patients, 135 presented at least one case of AP, which corresponds to a prevalence of 67.5%. Of the 5008 teeth examined, 296 had AP and 553 had ET. Therefore, considering the total number of teeth, AP and ET prevalences were 5.9% and 11%, respectively. Of the 553 endodontically treated teeth, 235 (42.5%) were associated with AP. Chi-square test showed a strong correlation between AP and ET (p<0.05). The 40-year-old age group was significantly the most prevalent (p<0.05). There was no association between AP and patient's sex (p>0.05). The maxillary incisors were the most affected group of teeth (p<0.05). AP had predilection for the maxilla and was strongly associated with endodontically treated teeth (p<0.05). The prevalence of apical periodontitis and endodontically treated teeth with AP was high and similar to the results of studies performed in other countries. O objetivo deste estudo foi investigar a prevalência de Periodontite Apical (PA) e sua associação com dentes tratados endodonticamente em residentes de São Luís, MA, Brasil. Foram selecionadas 200 séries completas de radiografias periapicais de arquivos de quatro protesistas e cinco periodontistas dos últimos 10 anos (1993-2003). O Índice Periapical (PAI) foi utilizado e a faixa etária, sexo, grupos dentais, localização de maior prevalência e associação aos dentes com tratamento endodôntico (TE) foram analisados. Os testes Cohen Kappa e qui-quadrado foram utilizados para análise estatística. Dos registros de 200 pacientes, 135 apresentavam algum caso de PA, resultando numa prevalência de 67,5%. Do total de 5008 dentes, 296 tinham PA e 553 tinham TE. Desse modo, a prevalência de PA foi de 5.8% e de TE foi de 11%. Dos 553 casos de dentes tratados endodonticamente, 235 (42.5%) estavam associados com PA. A faixa etária de 40 anos foi significativamente mais prevalente (p<0.05). Não houve associação entre PA e sexo (p>0.05). O grupo dental mais acometido foi dos incisivos superiores (p<0.05). A PA teve predileção pela maxila e apresentou-se fortemente associada com dentes tratados endodonticamente (p<0.05). A prevalência de periodontite apical e de tratamento endodôntico de dentes associado com PA encontrada neste estudo foi alta e está de acordo com resultados de estudos realizados em outros países.